Correlation Between Self Care Independence Level With Quality of Life of Diabetes Mellitus Patients In Inpatient Rooms - Herlina Luther Rande; Arsyawina; Hesti Prawita Widiastuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The method used is a correlational quantitative study with a cross-sectional approach using a sample of 38 taken by purposive sampling from 59 populations of Diabates Mellitus patients hospitalized at dr. Abdul Rivai Berau. Data analysis was carried out using the Pearson Product Moment test with a significance of 0.05. The results of the analysis showed that the average level of independence was 33.62 or Partly Compensatory, and the average quality of life was 78.175 or good quality of life. There is a significant relationship between independence (self-care) and the quality of life of Diabetes Mellitus patients in the inpatient room of RSUD dr. Abdul Rivai Berau has a significance value of 0.013 and a relationship strength level of 0.389 (low relationship